Complementary contrasts the glass and steel sculptures of Albert Paley - Oldknow, Tina; Greenhalgh, Paul 1955- (Museum of Glass, 2017)
"'Complimentary Contrasts: The Glass and Steel Sculptures of Albert Paley' highlights the significance of glass in the work of the celebrated sculptor Albert Paley. Though best known for his large-scale metal sculptures, Paley has incorporated glass in many works for over a decade. After beginning his career as a jewelry maker, Paley soon transitioned to furniture and freestanding sculpture. In the 1970s, Paley delved into large, site-specific works that blurred the line between sculpture and architecture. Despite disparity in size, Paley's collective artworks display a synergy of forms and philosophy, favoring natural curves and lines that defy their rigid materials. In 1999 Paley was invited to Pilchuck Glass School to collaborate with artist Dante Marioni. His experience utilizing fire to manipulate metal translated naturally into his glass design and allowed him to embrace the new material with ease. Since this initial introduction, Paley has collaborated with a number of glass artists and created over a hundred sculptures incorporating glass."--Amazon
Published to accompany the exhibition of the same name held at the Museum of Glass, Tacoma, Washington, from September 9, 2017 through September 2018
Keywords: Paley, Albert -- 1944-; Geschichte 2001-2016; Stahlplastik; Glas; Paley, Albert / Exhibitions; Paley, Albert / Interviews; Sculpture, Abstract / United States / 20th century / Exhibitions; Sculpture, Abstract / United States / 21st century / Exhibitions; Metal sculpture, American / 20th century / Exhibitions; Metal sculpture, American / 21st century / Exhibitions; Glass sculpture, American / 20th century / Exhibitions; Glass sculpture, American / 21st century / Exhibitions; Exhibition catalogs; Photobooks; Interviews; Bildband; Ausstellungskatalog -- Museum of Glass -- 09.09.2017-09.2018 -- Tacoma, Wash.